2022
DOI: 10.3390/microorganisms10091866
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Gut Bacterial Composition in People of Different Nationalities and Religions

Abstract: High-throughput sequencing has made it possible to extensively study the human gut microbiota. The links between the human gut microbiome and ethnicity, religion, and race remain rather poorly understood. In this review, data on the relationship between gut microbiota composition and the nationality of people and their religion were generalized. The unique gut microbiome of a healthy European (including Slavic nationality) is characterized by the dominance of the phyla Firmicutes, Bacteroidota, Actinobacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 151 publications
2
12
0
Order By: Relevance
“…Particularly, the genus Collinsella is presumed to have a direct causal relationship with UA. Collinsella aerofaciens , a representative species of the genus Collinsella , is abundant in the intestinal flora of Asians 12 and produces butyric, formic, lactic (LA), and acetic acids 13 . Indeed, C. aerofaciens has been reported to affect host health and disease 14 , and there are currently no reports of Collinsella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the genus Collinsella is presumed to have a direct causal relationship with UA. Collinsella aerofaciens , a representative species of the genus Collinsella , is abundant in the intestinal flora of Asians 12 and produces butyric, formic, lactic (LA), and acetic acids 13 . Indeed, C. aerofaciens has been reported to affect host health and disease 14 , and there are currently no reports of Collinsella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic variability as well as geographical location affect gut and oral microbiome composition [ 65 ], which can be also altered by obesity and overweight [ 66 , 67 ]. However, a previous study demonstrated that ethnicity-associated differences in the gut microbiota were stronger in lean subjects, while a difference in the gut microbiota was not shown in obese subjects from various ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, variation in environmental variables like temperature or humidity may cause changes in the host gut transcriptome and microbiome in concert, yet without a causal relationship between the transcriptome and gut microbiome. Host genotype also modulates both gene expression and microbiome composition (Tabrett & Horton, 2020), across a wide range of species (Chaston et al, 2016;Early et al, 2017;Fuess et al, 2021;Goodrich, Davenport, Beaumont, et al, 2016;Goodrich, Davenport, Waters, et al, 2016;Goodrich et al, 2014;Khan et al, 2019;Kurilshikov et al, 2021;Rajarajan et al, 2022;Small et al, 2019), and in humans can vary among populations and cultures (Syromyatnikov et al, 2022). Host genotype-by-environment effects may also modulate the microbiome (Hahn et al, 2022), though this possibility is under-researched.…”
Section: Discussionmentioning
confidence: 99%